2000
DOI: 10.1139/x00-039
|View full text |Cite
|
Sign up to set email alerts
|

Stand structure, invasion, and growth dynamics of bog pine (Pinus uncinata var. rotundata) in relation to peat cutting and drainage in the Jura Mountains, Switzerland

Abstract: A description of bog pine stands (Pinus uncinata Ramond var. rotundata (Link) Antoine) on uncut oligotrophic mires affected by drainage and nearby peat cuttings at three sites of the Jura Mountains (Switzerland) is given. In all sites, three situations were chosen: (i) central parts of the bogs, (ii) surfaces near cutting walls and bog margins, and (iii) intermediate situations. Population structures were characteristic for each situation. In the open and wet central parts of the bogs, trees were scattered, sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 26 publications
5
49
0
Order By: Relevance
“…Thus, the pinewood development on a large scale in the Jura bogs may represent a recent phenomenon. Extension of tall pinewood stands has been observed after the Jura bogs were affected by drainage [17]. This is confirmed by Hubschmid and Lang [23], Joray [25] and Reille [38], who emphasized that there has been a drastic increase in pine pollen abundance in the recent past within peat profiles, although pine (Pinus spp.)…”
Section: Introductionmentioning
confidence: 54%
See 3 more Smart Citations
“…Thus, the pinewood development on a large scale in the Jura bogs may represent a recent phenomenon. Extension of tall pinewood stands has been observed after the Jura bogs were affected by drainage [17]. This is confirmed by Hubschmid and Lang [23], Joray [25] and Reille [38], who emphasized that there has been a drastic increase in pine pollen abundance in the recent past within peat profiles, although pine (Pinus spp.)…”
Section: Introductionmentioning
confidence: 54%
“…latewood event years, which permit good cross-dating between bog pines. (2) Increase or decrease event years based on abrupt growth changes can be used as high frequency signals which may be interpreted in relation to climate, to human disturbances such as drainage [17], to unfavourable hydrologic conditions (this issue), or to take in evidence tree stand succession [19]. (3) Abrupt growth change curves maximise medium-term fluctuations, so that high-frequency signals are suppressed.…”
Section: Skeleton Plotmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of tree density, Freléchoux et al (2000) observed a low density of small pine trees in the central, wetter parts of bogs, compared to a higher density of taller pines in the drier rand of the bog. Bubier (1991) found similar results for Picea mariana (black spruce) for a raised bog in Vermont.…”
Section: Tree Height and Densitymentioning
confidence: 91%